PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN (SURVEI TERHADAP PENGGUNA LAPTOP MEREK TOSHIBA DAN PENGGUNA LAPTOP MEREK ACER) - Rizan, Mohammad; Prasetya, Rheza; Kresnamurti R. P., Agung (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2014)
The purpose of this research are: to know the description of product quality, service quality, and customer satisfaction of Toshiba Notebook Users and Acer Notebook Users, test empirically the influence of product quality toward customer satisfaction of Toshiba notebook users and Acer notebook users, test empirically the influence of service quality toward customer satisfaction of Toshiba notebook users and Acer notebook users, test empirically the influence of product quality and service quality toward customer satisfaction of Toshiba notebook users and Acer notebook users. Object of the research consist of Toshiba notebook users who has came to service center Toshiba and Acer notebook users who has came to service center Acer.The result of descriptive test shows that product quality and service quality Toshiba and Acer still less so that customer satisfaction also less. The hypothesis test shows: there is significant influence from product quality toward customer satisfaction; there is significant influence from service quality toward customer satisfaction; there is significant influence from product quality and service quality toward customer satisfaction. Keywords: product quality, service quality, customer satisfaction